Penyuluhan Kegawatdaruratan Maternal di Kelurahan Kedungmundu, Kecamatan Tembalang, Kota Semarang - Latifah, Hamnah; Purwanti, Indri Astuti; Kurnia Dewi, Maria Ulfa; Indrawati4, Nuke Devi (ADPERTISI, 2023)
Kedungmundu Village is a fostered area of the Faculty of Nursing and Health, Muhammadiyah University Semarang. Even though there is no maternal death, counseling about maternal emergencies must still be carried out as a coaching effort. The objective of this maternal emergency outreach activity is to increase participants' knowledge by 0.5 points. The method of this activity is lecture and question and answer. Before the lecture, a pretest was held and afterward, a posttest was carried out. Participants in this activity are high-risk pregnant women in the Kedungmundu Village. The results of data collection were analyzed by mean, standard deviation, percentage and dependent t test. The results of this activity show an increase in knowledge of 0.47 points. Even if the number of knowledge increases has reached the target when it is rounded up, the increase is not significant based on the results of the dependent t test (p = 0.356). Therefore, it is advisable to carry out community service activities in other areas where maternal mortality occurs.